PROTECTION OF FEMALE MIGRANT WORKERS: AN ANALYSIS OF POWER HEGEMONY BETWEEN INDONESIA AND SAUDI ARABIA - Fenny Kusuma Dewi; Meidi Kosandi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2025)
This study examines the hegemony of power and protection policies for female migrant workers through a case study of Indonesia and Saudi Arabia. Since the 1970s, the oil boom in Saudi Arabia has increased the demand for migrant workers, including those from Indonesia. The Kafala system implemented in Saudi Arabia gives employers full control over migrant workers, often leading to exploitation and human rights abuses. This study explores how the hegemony of power and economic factors influence the protection of female migrant workers. Using a qualitative approach, this research collects data through in-depth interviews and policy document analysis. The findings show that despite efforts by the Indonesian government to protect female migrant workers, the hegemony of power in Saudi Arabia and exploitative economic structures remain major obstacles. This study highlights the need for reform of the Kafala system and increased bilateral cooperation between Indonesia and Saudi Arabia to ensure better protection for female migrant workers. These findings make an important contribution to the literature on labor migration and protection policies and offer practical recommendations for policymakers in both countries.